ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Debby Eka Fitri Izmi; Uhud Darmawan Natsir; Nurman; Amiruddin Tawe; Anwar (Lafadz Jaya Publisher, 2023)
This study aims to determine the potential for bankruptcy in food and beverage companies listed on the Indonesia Stock Exchange using the Altman Z-Score method. This type of research is a quantitative approach. The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange. The samples in this study were 4 food and beverage companies which were included in the criteria set by the researcher. Data collection techniques are carried out with documentation. Data analysis technique using Altman Z-Score. The results of this study show that in 2017 there were 1 company in the